2015
DOI: 10.15344/2455-3867/2015/103
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cosmetic Plastic Surgery on Body Image and Psychological Well-Being: A Preliminary Study

Abstract: Background: The relationship between body image and cosmetic surgery represents a new generation of research on the psychological aspects of cosmetic surgery. Objective: This preliminary study intends to investigate the role of distress relating to body image in conditioning the levels of post-operatory patient benefit both the impact of cosmetic surgery on the state of psychological well-being and body image through the analysis of the differences between the pre and post-operative stages. Methods: The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 51 publications
0
11
0
2
Order By: Relevance
“…The results of this research are in agreement with other researches. [39][40][41] People who visit the clinic for cosmetic surgery often suffer from stress and have anxiety symptoms and even depression symptoms; furthermore, they recurrently have low body image and low self-esteem. People, who have not undergone any cosmetic surgery, have higher levels of frustration and negative self-evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this research are in agreement with other researches. [39][40][41] People who visit the clinic for cosmetic surgery often suffer from stress and have anxiety symptoms and even depression symptoms; furthermore, they recurrently have low body image and low self-esteem. People, who have not undergone any cosmetic surgery, have higher levels of frustration and negative self-evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…People, who have not undergone any cosmetic surgery, have higher levels of frustration and negative self-evaluation. [39][40][41] Given that in today's society, a huge emphasis is placed on attractiveness and physical fitness, and this matter has a profound effect on people's self-evaluation and brings on a substantial decrease in people's well-being. Whereas, people with a history of cosmetic surgery report lower anxiety and depression, and of course, enjoy higher well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, satisfaction of plastic surgery patients has often related to motivations and psychological characteristics. Assessing these features may help surgeons to decide which patients could be good psychological candidates for surgery [6] [54].…”
Section: Discussionmentioning
confidence: 99%
“…The primary stimulus for individuals to undergo rhinoplasty is more satisfied with their own appearance and improving their psychosocial functioning (von Soest et al, 2009). Several studies have demonstrated that rhinoplasty may improve quality of life (QoL), self-esteem, body image and social interactions (Esteves et al, 2017). A study showed that cosmetic surgery improves body image and self-esteem but it does not have any effect on psychological problems (von Soest et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A study showed that cosmetic surgery improves body image and self-esteem but it does not have any effect on psychological problems (von Soest et al, 2009). A preliminary study showed that the severity of body image distress may negatively impact on satisfaction with the outcome of the surgery (Di Mattei et al, 2015). A qualitative study in Iran focused on paradigm models to explain conditions, processes, and consequences of Rhinoplasty among the participants (Pournasiri, 2016) but it did not present a deep understanding from the studied phenomenon to explore the core concept so that it focused only on some general categories.…”
Section: Introductionmentioning
confidence: 99%